The effect of C:P ratio of plant residues added to soils of contrasting phosphate sorption capacities on P uptake by Panicum maximum (Jacq.) - Umrit, Gunshiam; Friesen, Dennis K. (Springer, 1994)
Reutilization of P from Setaria sphacelata residues having C:P ratios of 704:1, 227:1, and 77:1 was studied using a reverse 32P-isotopic dilution technique in the greenhouse. Residues were incorporated into two highly weathered Malaysian soils (Ultisols and Oxisols) treated with five levels of inorganic P labeled with 32P and cropped with Panicum maximum (Jacq.). Yield of dry matter, total P, and 32P activity of Panicum was monitored through four cuttings spanning a period of approximately 13 weeks. Panicum yields and residue-P uptake were depressed by high and medium C:P ratio residues at the first cutting but recovered in subsequent cuttings. General adequacy of P concentrations in the affected tissue and its failure to respond to applied inorganic P among other factors suggest that the initial yield depression was not induced by P immobilization. The fractional percentage of P derived from residues increased with increasing P content of residues at all cuttings. Similarly, L-values were consistently greater on residue-treated soils. Residue P had greater effects on the soil with lower than on that with higher P-sorbing capacity. Changes in residue P uptake, L-values, and extractable P in soil between successive cuttings suggest a rapid release of a large amount of easily mineralizable residue P within the first 4 weeks, with the subsequent P release being much slower by comparison.